92.7k views
1 vote
Y = x + 312x + y = -6

User Zellus
by
5.9k points

1 Answer

3 votes

We have a system of linear equations.

The most simple way to solve it is by substitution:


\begin{gathered} y=x+3 \\ 12x+y=-6 \\ \\ 12x+(x+3)=-6 \\ 12x+x+3=-6 \\ 13x+3=-6 \\ 13x=-6-3=-9 \\ x=(-9)/(13) \\ \\ y=x+3=(-9)/(13)+3=(-9+3\cdot13)/(13)=(-9+39)/(13)=(30)/(13) \end{gathered}

The values for the unknowns are x=-9/13 and y=30/13

User Hasan Barary
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.